The Effects of Pollution and Business Environment on Firm Productivity in Africa - Soppelsa, Maria E.; Lozano-Gracia, Nancy; Xu, L. Colin (World Bank, Washington, DC, 2019)
This paper explores the links between city competitiveness and air pollution and the business environment. Because competitive cities not only attract more productive firms, but also facilitate their business, the paper look at firm performance as a proxy for city competitiveness. It focuses on African firms, because this region is developing fast and experiencing increasing pollution levels and the effects of agglomeration economies. The analysis finds two interesting results. First, the negative association between air pollution and firm performance can be seen at lower than expected levels of pollution. Second, the effects of capacity agglomeration on labor productivity growth are stronger compared to other regions. These findings suggest that cities in this region should address pollution issues soon, as they continue to grow fast and pollution levels are becoming an increasing concern.